An laboratorial investigation of induced seismicity characteristics in EGS hydraulic fracturing. (November 2022) - Cheng, Yuxiang; Xu, Tianfu; Zhang, Yanjun; Shangguan, Shuantong; Feng, Bo
Highlights: Induced seismicity mitigation methods for EGS development are investigated based on laboratorial acoustic emissions. Acoustic emission characteristics are analyzed by true-triaxial hydraulic fracturing experiments under different injection flow rates, temperatures and confining stresses conditions. Induced seismic risk is positively correlated with the injection flow rate, negatively correlated with the confining stress. Abstract: Geothermal energy has attracted more attention lately. During geothermal energy extraction from Enhanced Geothermal Systems (EGS), hydraulic fracturing has become a standard reservoir stimulation technology. Induced seismicity during this stimulation process is inevitable and has been documented worldwide. Sometimes, large magnitude earthquakes may be induced during hydraulic fracturing process, such as the EGS engineering project failure in Pohang and Basel. The induced seismicity has already become the main obstacle for the development of EGS. Therefore, it is necessary to investigate the characteristics of induced seismicity to find seismic mitigation strategy. To advance this mitigation research, large-size Hot Dry Rock (HDR) formation environment is established to analyze induced seismicity characteristics. Acoustic emission (AE) is used to simulate induced seismicity in field, the AE characteristic parameters are analyzed under different experimental conditions. The results of AE indicate that high injection flow rate and high confining stress could increase the maximum induced earthquake magnitude, the induced seismic risk will increase in these two circumstances. The increase of temperature do not obviously affect AE occurrence and slightly decreases the maximum AE energy which means that hydraulic fracturing in high temperature reservoir will not increase seismic risk. These results of this study can provide some reasonable guidance on the application of induced earthquake mitigation in field-scale HDR hydraulic fracturing operation.